A Fully Integrated Humidity Sensor System-on-Chip Fabricated by Micro-Stamping Technology - Chih-Ting Lin; Shey-Shi Lu; Yu-Jie Huang; Che-Wei Huang (Sensors, 2012)
A fully integrated humidity sensor chip was designed, implemented, and tested. Utilizing the micro-stamping technology, the pseudo-3D sensor system-on-chip (SSoC) architecture can be implemented by stacking sensing materials directly on the top of a CMOS-fabricated chip. The fabricated sensor system-on-chip (2.28 mm × 2.48 mm) integrated a humidity sensor, an interface circuit, a digital controller, and an On-Off Keying (OOK) wireless transceiver. With low power consumption, i.e., 750 μW without RF operation, the sensitivity of developed sensor chip was experimentally verified in the relative humidity (RH) range from 32% to 60%. The response time of the chip was also experimentally verified to be within 5 seconds from RH 36% to RH 64%. As a consequence, the implemented humidity SSoC paves the way toward the an ultra-small sensor system for various applications.